2022
DOI: 10.1016/j.omto.2021.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Acquired chemoresistance can lead to increased resistance of pancreatic cancer cells to oncolytic vesicular stomatitis virus

Abstract: Vesicular stomatitis virus (VSV) is a promising oncolytic virus (OV) against different malignancies, including pancreatic ductal adenocarcinoma (PDAC). Our previous studies have demonstrated that VSV-based OVs are effective against the majority of tested human PDAC cell lines. However, some PDAC cell lines are resistant to VSV. PDAC is one of the deadliest types of human malignancies in part due to intrinsic or acquired chemoresistance. Here, we investigated how acquired chemoresistance impacts the efficacy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…As VSV-based OV therapy becomes a more commonly tested therapeutic option in clinical trials (Clinicaltrials.gov trials NCT01628640, NCT03120624, NCT04046445, NCT03865212, NCT03017820, and NCT03647163), it is necessary to better understand how the effectiveness of VSV-based OV therapy is affected by the chemoresistance status of cancer cells. It has been observed in our previous studies and others ( 48 , 55 , 57 , 66 ) that the level of chemotherapeutic drug resistance may correlate with the level of antiviral signaling in cancer cells. This phenomenon is important to consider when determining the best therapeutic regimen for cancer patients.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…As VSV-based OV therapy becomes a more commonly tested therapeutic option in clinical trials (Clinicaltrials.gov trials NCT01628640, NCT03120624, NCT04046445, NCT03865212, NCT03017820, and NCT03647163), it is necessary to better understand how the effectiveness of VSV-based OV therapy is affected by the chemoresistance status of cancer cells. It has been observed in our previous studies and others ( 48 , 55 , 57 , 66 ) that the level of chemotherapeutic drug resistance may correlate with the level of antiviral signaling in cancer cells. This phenomenon is important to consider when determining the best therapeutic regimen for cancer patients.…”
Section: Discussionmentioning
confidence: 52%
“…We have recently shown that some human PDAC cell lines, which acquire resistance to chemotherapeutical drugs, can also simultaneously develop resistance to OV therapy ( 48 ). In addition, although the analyses of 10 different human PDAC cell lines showed no statistically significant correlation between their resistance to gemcitabine and VSV, 4 PDAC cell lines most resistant to VSV were also among 5 PDAC cell lines most resistant to gemcitabine ( 48 ). The chemoresistance of PDACs is one of the major reasons for the poor survival outcomes of PDAC patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…STAT2 and its associated ISGs are overexpressed in several chemoresistant cancer types. Gemcitabine resistance in pancreatic ductal adenocarcinoma (PDAC) cells and subsequent resistance to vesicular stomatitis virus (an oncolytic viral therapy) correlates with an accumulation of STAT1 and STAT2 as well as upregulation of a particular subset of ISGs: MX1, MX2, IFITM1, IFIT1, and IFI44 [ 59 ]. Interestingly, enhanced expression of these genes occurs without upregulation of IFN-α or IFN-β.…”
Section: Stat2 and Chemoresistancementioning
confidence: 99%
“…In a study ( 228 ), interrogated the VSV resistance in highly chemoresistant pancreatic cancer cell lines. They identified that upregulated interferon-stimulated genes cause VSV resistance in pancreatic cancer.…”
Section: Oncolytic Virus Therapymentioning
confidence: 99%